TO CALCULATION OF CONJUGATED HEAT EXCHANGE IN FLAMING FURNACES OF CHAMBER TYPE - Kayukov, Yurii; Ivanov, Viktor; Ryzhkov, Vadym; Nazarenko, Irina (Scientific Journal "Metallurgy", 2021)
During planning of new and reconstruction of operating flaming chamber furnaces it is necessaryto provide the conditions for achievement of high evenness heating metals in the momentof output from the work volute furnace. For the evaluation of metal heating evenness at the differentmodes of work furnaces of noted type a mathematical model, which is based on the decisionof the connected task of external and internal heat exchange at discrete time is worked out.The zonal model of external heat exchange in the work volume of the noted furnace is given bythe closed system, which is created by opaque solids, divided by an absorptive-radiate medium.The system is divided into five volume areas of torch and combustion gas, five flat superficialareas of metal and seventeen flat superficial areas of furnace lining. Within the limits of everysuperficial area absolute temperature of heater medium, concentration of its absorptive-radiatecomponents, accepted fixed. The volume radiation of heater medium is replaced by the equivalentdiffuse radiation of imaginary surface, which has a degree of blackness which has a degreeof blackness which equals the degree of blackness for volume area. Except for that, enteredconditional absolutely black surfaces which separate I volume area from contiguous j volumeareas. The calculations of radiation heat exchange within the limits of separate subsystem executedwith the use of resolving zonal method. One of directions for quality metal heating in thefurnaces of chamber type there is impulsive input of fuel in the period of self-control of metal.Application of the noted mode for heating of furnace allows to promote a temperature in the laston motion of torch to the volume heater area comparatively with the typical mode of heating,that accompanied by the increase of thermal content of metal in this area.